A Penyelesaian Sengketa Tanah melalui Mediasi di Kantor Pertanahan Kota Salatiga - Krisanto, Yakub Adi (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
Mediation is an alternative settlement implemented by the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency to optimize the resolution of land cases. One of them is by issuing Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 11 of 2016 concerning Settlement of Land Cases. Land cases that can be resolved through mediation do not only originate from the Ministry's initiative, but are also based on public complaints. The Land Office is at the forefront in carrying out mediation to improve the resolution of land cases in Indonesia. The Salatiga City Land Office has taken a role in settlement efforts through mediation. Although the results of the mediation carried out have not yet reached an agreement or peace.